Challenges in opioid therapy implementation: national survey of palliative care consultation services - Müller, Evelyn; Gahr, Susanne; Schnell, Annette; Schildmann, Eva; Boehlke, Christopher; Roch, Carmen (BMC Palliative Care, 2025)
Background: Palliative care consultation services in hospitals can improve symptom control in patients with advanced illness by recommending or prescribing WHO step III opioids. However, effective treatment depends on the attending ward team which implements these therapies. While deviations from the opioid therapy recommended by the palliative care service and also treatment errors are often an issue in everyday life, there is no current data on the extent of the problem. This study explored the experiences of palliative care consultation services with the implementation of opioid recommendations by the attending ward team. Methods: The questionnaire was developed through a multi-step process, including e.g. literature analysis and pre-testing with cognitive interviews. A closed national online survey was conducted via the SoSci Survey platform. All palliative care consultation services registered with the German Association for Palliative Medicine were invited to participate in November 2024, with a reminder sent three weeks later. Results: The survey was fully completed by 39 of 85 consultation services (response rate: 46%; 21 university, 18 general hospitals). Thirty-one consultation services provide recommendations for opioids, eight provide prescriptions. Most (23 of 39) reported a rather high or very high need for improvement in implementing opioid recommendations (4-point Likert-scale, very low – very high). Common deviations included “no implementation at all,” “lower dose,” and “non-implementation of medications to prevent side effects.” “Inexperience or reservations about opioid therapy among attending ward staff” was the most frequently cited reason, named by 35 of 39 palliative care consultation services as occurring “sometimes” or “often” (5-point Likert-scale, “(almost) never” – “(almost) always”). Participants highlighted need for improvement in regard to symptom assessment, prescribing and use of PRN (pro re nata; on demand) medication, continuity of opioid therapy at discharge, and opioid treatment in the dying phase. Consultation services providing opioid recommendations reported significantly more frequent deviations from recommendations and a greater need for improvement compared to those prescribing opioids. Conclusion: Despite a 46% response rate, limiting generalizability, the frequent reporting of collaboration challenges between palliative care consultation services and attending ward teams regarding opioid-based symptom control highlights a relevant problem. Targeted training could improve implementation and symptom management.
CRIS-Team Scopus Importer:2025-10-31
Keywords: Analgesics; Consultation; Opioid; Palliative care; Palliative medicine